2015
DOI: 10.4141/cjas-2014-184
|View full text |Cite
|
Sign up to set email alerts
|

Effect of post-weaning residual feed intake classification on grazed grass intake and performance in pregnant beef heifers

Abstract: K. 2015. Effect of post-weaning residual feed intake classification on grazed grass intake and performance in pregnant beef heifers. Can. J. Anim. Sci. 95: 369Á381. There is limited knowledge of how cattle tested for feed efficiency under drylot conditions perform when they graze on summer pasture. Residual feed intake adjusted for end of test backfat thickness (RFI fat ) was determined on 171 beef crossbred heifers under drylot conditions over 2 yr using an automated system. Upon completion of the test, the 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 27 publications
(33 reference statements)
1
22
0
1
Order By: Relevance
“…Similarly, Morris et al (2014) reported no difference in herbage intake in grazing lactating beef heifers from highand low-RFI selection lines. In contrast, Manafiazar et al (2015) reported that heifers ranked as low-RFI in an outdoor drylot offered a barley silage-based diet had a lower intake of grazed herbage when subsequently measured as pregnant replacement heifers. Reasons for the discrepancies in DMI between the confined and grazing dietary phases in the majority of the aforementioned studies may be attributed to: (i) the re-ranking per se of animals for RFI over time (maturity); (ii) differences in diet type and thus, associated intake and digestion characteristics; (iii), changes in the physiological state of the animals and, finally, and perhaps most importantly (iv) the inherent difficulty in accurately quantifying herbage intake in grazing cattle (Lawrence et al, 2012).…”
Section: Maternal Traits and Fertilitymentioning
confidence: 91%
“…Similarly, Morris et al (2014) reported no difference in herbage intake in grazing lactating beef heifers from highand low-RFI selection lines. In contrast, Manafiazar et al (2015) reported that heifers ranked as low-RFI in an outdoor drylot offered a barley silage-based diet had a lower intake of grazed herbage when subsequently measured as pregnant replacement heifers. Reasons for the discrepancies in DMI between the confined and grazing dietary phases in the majority of the aforementioned studies may be attributed to: (i) the re-ranking per se of animals for RFI over time (maturity); (ii) differences in diet type and thus, associated intake and digestion characteristics; (iii), changes in the physiological state of the animals and, finally, and perhaps most importantly (iv) the inherent difficulty in accurately quantifying herbage intake in grazing cattle (Lawrence et al, 2012).…”
Section: Maternal Traits and Fertilitymentioning
confidence: 91%
“…Although RFI is repeatable across different stages of the production cycle when animals are offered the same diet (Kelly et al, 2010b), there is limited information on whether animals rank similarly for RFI, or, indeed, its component traits across diets differing in energy density and chemical composition. A recent study from Manafiazar et al (2015) showed that beef heifers ranked as low RFI under drylot conditions, when offered a barley silage and steam-rolled barley TMR, also consumed 5.3% less forage than high-RFI heifers in a follow-up experiment when meadow bromegrass pasture was offered. In contrast, Meyer et al (2008) observed no difference in grazed forage intake between beef cattle of known divergent RFI classification, although these authors did acknowledge that the methodology used to estimate pasture DMI may have been a limiting factor in that study.…”
Section: Feed Intake and Residual Feed Intake Classificationmentioning
confidence: 99%
“…The dataset also had final backfat thickness, and diet ingredient composition and dry matter (DM; %) and metabolizable energy (ME; MJ kg −1 DM) content. Parts of these data were used previously in numerous publications (e.g., Basarab et al 2003Basarab et al , 2011Manafiazar et al 2015). The dataset consisted of 387 492 daily feed intakes from 2 066 bulls, 1 011 replacement heifers, and 2 078 feeder heifers, and steers making a total of 5 155 animals in 85 contemporary groups (CGs).…”
Section: Data Acquisition and Animalsmentioning
confidence: 99%
“…After this data editing, a total of 4842 animals (1917 bulls in 42 CG; 1972 feeders in 27 CG; and 953 replacement heifers in 16 CG) remained for analysis. Diet compositions and details of feed test procedures were previously described by Basarab et al (2003Basarab et al ( , 2011 and Manafiazar et al (2015). In short, each animal was tagged with a half-duplex radio frequency identification (RFID) tag, and daily individual feed intake data were recorded by the GrowSafe system (GrowSafe Systems Inc., Airdrie, AB, Canada).…”
Section: Data Acquisition and Animalsmentioning
confidence: 99%
See 1 more Smart Citation